Do warranties influence perceptions of service quality?: a study of the automobile repair and service industry - Andaleeb, Syed Saad; Basu, Amiya K. (© 1998 Published by Elsevier Ltd., 2016)
This article was published in the Journal of Retailing and Consumer Services [© 1998 Published by Elsevier Ltd. ] and the definite version is available at : http://doi.org/10.1016/S0969-6989(97)00072-6 The Journal's website is at: http://www.sciencedirect.com/science/article/pii/S0969698997000726